2014
DOI: 10.4161/biom.28871
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of mathematical models of thin film growth and surfaces

Abstract: The morphology of thin films has been extensively studied in the last years. The properties of a thin film are closely related to its microstructure, especially to its morphology and surface roughness. Optical reflectivity, conductivity, and porosity are characteristics that depend on the film structure. The knowledge of atomistic details of the thin film growth process is useful for the development of new techniques and the control of thin films and new materials. Models of growth process are very powerful to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The BD models date back to [57] and [54], where a variation of the model was proposed to describe sedimentation and aggregation in colloids. Models of this type have been applied to study formation, morphology, and surface roughness of sedimentary rocks [22] and thin films [21, 34].…”
Section: Introductionmentioning
confidence: 99%
“…The BD models date back to [57] and [54], where a variation of the model was proposed to describe sedimentation and aggregation in colloids. Models of this type have been applied to study formation, morphology, and surface roughness of sedimentary rocks [22] and thin films [21, 34].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Based on various approaches, mathematical models developed for the determination of lm growth were illustrated by Forgerini and Marchiori (2014). 4 The microstructural evolution of lm growth is governed by number of different processes, such as nucleation, coalescence, competitive grain growth, and recrystallization. 5 In addition to these processes, it is reported that processes like adsorption and surface reaction not only promote lm growth but also inuence the surface properties of thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal growth or island growth is when individual dispersed crystals grow from many nuclei, but when this occurs the final orientation is not always determined. This can later be changed, when it grows as part of a polycrystalline structure and there is for the collective behavior of the polycrystalline film a dependence of for instance grain size and surface conditions [41,44].…”
Section: 7 Thin Film Growthmentioning
confidence: 99%